Intravenous Ketamine for Cancer Pain Management, Including Flares During the COVID-19 Pandemic: A Retrospective Study. Issue 7 (4th June 2021) - Oh, Daniel; Haffey, Paul; Patel, Ankur; Gulati, Amitabh
Abstract: Objectives: Cancer-related neuropathic pain (CNP) affects an increasing proportion of cancer patients, given improved survival, but it remains difficult to treat. There are no studies on an extended intravenous ketamine protocol and its synergies with common neuropathy treatments to treat CNP. This study aims to 1) evaluate the safety and effectiveness of an intravenous ketamine protocol to treat refractory CNP and 2) uncover synergies between ketamine and common neuropathy treatments. Methods: This is a single-center, retrospective review of 57 patients and 192 infusions, with prospective follow-up on 14 enrolled patients during the coronavirus disease 2019 (COVID-19) pandemic. Results: The etiologies of CNP were as follows: 13 from tumor compression, 25 with chemotherapy-induced peripheral neuropathy, 13 from surgery, and 6 from radiation therapy. Overall, 42 of 57 patients (73.7%) were responders, and 71.8% of responders received >3 weeks of pain relief on their last infusion. Analysis of adjuvant treatments revealed that the combination of serotonin-norepinephrine reuptake inhibitors and ketamine resulted in an increase in responders compared with nonresponders ( P  < 0.01). Adverse events occurred in 32 of 192 infusions (16.7%). All side effects self-resolved or resolved with intervention per the adverse events protocol. During the pandemic, all 14 currently enrolled patients did not receive ketamine infusions. Thirteen of the 14 patients returned to baseline pain, with 61.5% increasing medications. All experienced worsened function, mobility, mood, or anorexia. Conclusion: Intravenous ketamine may be a safe and effective adjuvant treatment for CNP, especially with serotonin-norepinephrine reuptake inhibitors. Larger, prospective studies are warranted and should explore parameters to help prognosticate response to ketamine infusions.